Tradisi Seni Patrol dan Identitas Budaya Kampung Bandulan di Kota Malang - Maftuchin, Annise Sri; Budiyanto, Ary (Studi Budaya Nusantara, 2017)
ABSTRACT Local traditions are not always weakened traditional form of culture in the global area. Bandulan patrol art tradition in Malang is one of them, this art is growed by invented tradition process with festival mode. Invented tradition is Hobwbawn (2000) concept which describe of the appearance of a tradition that is not viewed as old. This patrol art traditions research is intended to answer a research problem about how Bandulan local society make create in a new identity on the global area? To answer these problems, researchers used anthropological methode where observation, participatory observation and in-depth interview are used by the research. The method form use to describing phenomena in the Bandulan society. These results indicate the existence of a process invented tradidition going on basis and is fully supported by the process of globalization that exist in the festival media. patrol Art tradition which processed by invented is development of a local patrol sahur tradition , that the development is processed by contact culture who concepted by Liep (2001) helped to describe for process of establishing the identity of of Hall concept (1990). The pattern is related identity as being Bandulan confronted with foreign cultures and global cultures. This mixed process form is fused into the end result of a culture intact where local taste of culture still feels strong up there. The tradition of the art patrol appear to be a identity product of the becoming on the art festival patrol in Bandulan. Bandulan art patrol have different characteristics with ul–daul music though near same , but the Bandulan art patrol has a different style of music that have identic character. Bandulan art patrol has a identic style of typical of art music patrol . Characteristics campursari music what growing up in Bandulan and the slowler rhythm beats than ul-daul be identic style from the creation of identity what have style of local culture which can survive in global area that is true.